Eksplorasi Budaya dan Sejarah: Studi Tentang Objek Wisata di Kuil Gangoji - Yusuf, Muhammad (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2023)
The oldest large-scale temple in Japan is Asukadera (Gangoji Temple), which has a five-story pagoda (tō), a main hall (kondō) encircled by a covered corridor (kairo), an assembly hall (kōdō), and a number of auxiliary structures. And the gate (mon), which serves as the Asukadera complex's entryway. It took a while to create this temple, which was built with the assistance of laborers from Paekche. Because it takes a lot of labor to construct a big temple. Building construction must begin with the preparation of building materials such wood, stone, clay, and others before work can begin. The first pagoda was constructed first, then the kond and other structures. Every structure in Asukadera serves a specific purpose. It is used to store holy items, much to a kondō, which is used to house artwork or Buddha statues. Pagoda used as a repository for Buddhist artifacts. Assembly hall (kōdō), used for meetings or as a study location. The overall goal of this article is to learn more about the origin and history of Asukadera's construction as well as the purpose and significance of each of the complex's buildings. This essay makes use of both the library approach and the findings from related studies.